Adaptive Design for Phase II/III Platform Trial of Lassa Fever Therapeutics - Josephine Bourner; Michel Vaillant; Alex Paddy Abdel Salam; Marie Jaspard; Camille Fritzell; Shevin T. Jacob; Tom E. Fletcher; Michael Ramharter; Nnennaya Ajayi; Sylvanus Okogbenin; Cyril Erameh; Donald Grant; et al. (Emerging Infectious Diseases, 2025)
The current recommendation for treating Lassa fever with ribavirin is supported only by weak evidence. Given the persistent effects in areas with endemic transmission and epidemic potential, there is an urgent need to reassess ribavirin and investigate other potential therapeutic candidates; however, a robust clinical trial method adapted to Lassa fever epidemiology has not yet been established. We propose an adaptive phase II/III multicenter randomized controlled platform trial that uses a superiority framework with an equal allocation ratio and accounts for challenges selecting the primary end point and estimating the target sample size by using an interim analysis.